A social network analysis of fan engagement in ‘Queen of Tears’ - Tabitha Hemastuti; Roro Retno Wulan (Faculty of Communications Science, Dr. Soetomo University, 2026)
The development of digital media has transformed how fans interact with and consume popular culture, particularly Korean dramas. Queen of Tears exemplifies an online marketing strategy that leverages the power of YouTube as a social network platform. Fans are not merely passive consumers; they also actively participate in activities that support the drama. The purpose of this study is to analyse the fan communication networks surrounding the Korean drama Queen of Tears on the Netflix K-Content YouTube channel, specifically the video ‘Queen of Tears Cast Reveals Secrets to Each Other | Office Hours | Netflix’. This research employed the Social Network Analysis (SNA) using Gephi 9.0 to process comment data. The results revealed two types of communication network patterns: wheel communication patterns and chain communication patterns. The main actor within the network is @fourleafclover-ww1mm, who demonstrates significant influence in conversations on the Netflix K-Content YouTube channel, as indicated by centrality indicator values. These findings highlight the potential effectiveness of YouTube as a platform for fostering fan engagement and promoting Korean dramas. Theoretically, this study contributes to the development of social network analysis in fandom and digital media research. In practice, it provides insights into how fan interactions can be optimised for content promotion strategies in the entertainment industry.